Morphological Patterns of the Long Limb Bones in the Lesser Bandicoot Rat, Bandicota Bengalensis (Rodentia: Muridae) (Bangladesh Journal of Zoology, 2023)
We examined the morphological patterns of long limb bones in the Lesser Bandicoot rat (Bandicota bengalensis) using univariate, bivariate and multivariate statistical analyses. A total of 18 morphometric measurements were taken using 30 adult specimens (11 males and 19 females) of B. bengalensis. The univariate analysis revealed non-significant right-left difference in the longest limb bones. Therefore, right side limb bones were used for further analyses. For most of the limb bone measurements, the mean values of the males were slightly larger than that of the females. However, the coefficient of variation did not differ significantly between the sexes. Most measurements of the fore limb and hind limb bones were significantly correlated with the length of respective bones. Allometric analysis exhibited isometry for many of the variables of humerus, ulna, femur, and tibia against the length of respective bones. These trends were also implied by the principal component analysis, as high factor loadings were observed for 80% and 75% variables of the forelimb and hindlimb, respectively. The epicondylar regions of the stylopodial bones (humerus and femur) and the width of radius showed non-significant correlation and/or negative allometry. Finally, our results suggest slightly male-biased sexual size dimorphism in the long limb bones and the growth patterns of the bone parts are greatly variable might be linked to the individual bone functions.Bangladesh J. Zool. 51(2): 191-203, 2023